Multifunctional graphitic tracks on flexible polymer sheet as strain, acoustic vibration and human motion sensor. (November 2019) - Khurana, Vaibhav; Kaur, Manpreet; Kumar, Suresh; Gupta, Dipti; Goswamy, J.K.
Graphical abstract: Highlights: Low cost flexible pencil drawn multifunctional sensor fabricated on PET sheet. Tunable resistor of graphitic film fabricated on PET sheet. Excellent sensitivity achieved. Sensor can detect human muscle motion efficiently. Abstract: In this contribution, we demonstrate a low cost, scalable, flexible and reproducible multifunctional sensor developed by dry drawing pencil traced graphitic track on polyethylene terephthalate (PET) sheet. Characterization of the graphitic tracks on PET is performed using X-ray diffractometry, Raman spectroscopy and Fourier transform infrared spectroscopy techniques. The graphitic tracks by varying number of drawing iterations showed electrical tunable resistance characteristics. As an acoustic vibration sensor, the sensing platform displayed the sensitivity of 1.23 × 10 −3 Hz −1, current switching capability of 1.0:1.35 at 150 Hz added with an acceptable response time of 37 ms. It has shown considerable electrical resistance change in response to human muscle movement. Resistance change with strain was measured by motorized force and torque tester. The present sensor has a capability to replace existing high-cost sensors employed for the same applications.